Intra-Arterial Thrombolysis Vs. Mechanical Thrombectomy in Acute Minor Ischemic Stroke Due to Large Vessel Occlusion - Sun, Dapeng; Huo, Xiaochuan; Raynald,; Wang, Anxin; Mo, Dapeng; Gao, Feng; Ma, Ning; Miao, Zhongrong (Frontiers in Neurology, 2022)
Background The efficacy and safety of mechanical thrombectomy (MT) in acute large vessel occlusion (LVO) patients with minor stroke (NIHSS ≤ 5) remains undetermined. We aimed to compare the efficacy and safety of intra-arterial thrombolysis (IAT) alone vs. MT for LVO patients with minor stroke. Methods Patients were selected from the Acute Ischemic Stroke Cooperation Group of Endovascular Treatment (ANGEL) registry, a prospective multicenter registry study, and divided into MT and IAT alone groups. We compared the outcome measures between the two groups, including 90-day functional outcome evaluated by the modified Rankin Scale (mRS), the final recanalization level, intracranial hemorrhage, and mortality within 90-days by logistic regression models with adjustment. Besides the conventional multivariable analysis, we performed a sensitivity analysis by adjusting the propensity score to confirm our results. The propensity score was derived using a logistic regression model. Results Of the 120 patients, 63 received IAT alone and 57 received MT as the first-line treatment strategy. As compared to MT group, patients in the IAT alone group were associated with a higher chance of 90-day mRS 0-2 [93.7% vs. 71.9%, odds ratio (OR) = 4.75, 95% confidence interval (CI): 1.20–18.80, P = 0.027], a high chance of 90-day mRS 0-3 (96.8% vs. 86.7%, OR = 11.35, 95% CI: 1.93–66.86, P = 0.007), a shorter median time from puncture to recanalization (PTR) (60 min vs. 100 min, β = −63.70, 95% CI: −81.79– −45.61, P < 0.001), a lower chance of any intracranial hemorrhage (ICH) within 48 h (3.2% vs. 19.3%, OR = 0.15, 95% CI: 0.03–0.79, P = 0.025), and a lower chance of mortablity within 90 days (1.6% vs. 9.2%, OR = 0.05, 95% CI: 0.01–0.57, P = 0.016). Similarly, the sensitivity analysis showed the robustness of the primary analysis. Conclusions Compared with MT, IAT may improve 90-day clinical outcomes with decreased ICH rate and mortality in LVO patients with minor stroke.